KEDUDUKAN MAHKAMAH KONSTITUSI DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA - Virto Silaban; Kosariza (Universitas Jambi, Fakultas Hukum, 2021)
This study aims to find out and analyze the position of the Constitutional Court in accordance with the 1945 Constitution of the Republic of Indonesia, regulated further in Law Number 8 of 2011. To find out the implications of the Constitutional Court's decision which is final and binding. The problem is how is the position of the Constitutional Court in the constitutional system of the Republic of Indonesia based on the 1945 Constitution of the Republic of Indonesia and regulated further in Law Number 8 of 2011? What are the implications of the Constitutional Court's decision which is final and binding? This research approach is Normative Juridical, in this study the author will examine the position of the Constitutional Court in the constitutional system of the Republic of Indonesia and the implications of the Constitutional Court's decision which is final and binding. The results of this study are that the position of the Constitutional Court in the constitutional system of the Republic of Indonesia based on the 1945 Constitution of the Republic of Indonesia is a high state institution encompassed by the judicial authority together with the Supreme Court and the judiciary below which is tasked with upholding the supremacy of the constitution. Decisions issued by the Constitutional Court are final and binding on the principle of Erga Omnes. Conclusion: the position of the Constitutional Court in the constitutional system of the Republic of Indonesia is a judicial institution that runs the judicial power and is separate from the Supreme Court. The decision of the Constitutional Court is final and binding on the principle of erga omnes. Suggestion: the need to affirm the process of filling the position of judge of the Constitutional Court and the prohibition of judges of the Constitutional Court to create the independence of the Constitutional Court. The need for communication between the Constitutional Court and other state institutions for the execution of the Constitutional Court's decision, so that every decision issued by the Constitutional Court erga omnes.